PENGARUH PRODUCT KNOWLEDGE DAN TREND HEALTHY LIFESTYLE TERHADAP MINAT BELI PRODUK UMKM HOLLY JELLY (Studi Kasus Pada Konsumen Gen Z di Surabaya) - Septianan, Endra Wahyu; Firdaus, Febriski Dwi; Madina, Aldira Layza; Wardana, Faurelia Audina; Saddam, Muhammad (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
Despite their size, SMEs (Small and Medium-sized Enterprises) wield an outsized impact on Indonesia's economy, driving growth and innovation amidst complex challenges. This study investigates the influence of product knowledge and the trend of healthy lifestyles on the purchase intention of Holly Jelly—one of the SMEs, an innovative healthy jelly brand targeting Gen Z consumers in Surabaya. Two key factors are hypothesized to drive purchase intention: product knowledge, defined as consumer awareness and understanding of Holly Jelly's attributes, and the trend of healthy lifestyles, reflecting Gen Z's growing preference for health-conscious choices. This study aims to examine the independent and interactive effects of these factors on purchase intention through quantitative research methodologies. A purposive sampling method strategically selected 50 Gen Z consumers in Surabaya to participate in an online google form survey.To ensure data quality, classical assumption tests for normality, multicollinearity, and heteroscedasticity were conducted prior to linear regression analysis. The analysis revealed a significant influence of the trend of healthy lifestyles (p = 0.041) on purchase intention, confirming the growing importance of health consciousness among Gen Z consumers. However, product knowledge (p = 0.295) did not show a significant independent effect. This suggests that while general health awareness may drive purchase intention, specific knowledge about Holly Jelly's features may not be as influential.